Fast Pyrolysis of Torrefied Leucaena leucocephala Wood in a Bubbling Fluidised-Bed Reactor - Pattiya, Adiak (Srinakharinwirot University Engineering Journal, 2020)
In this work, torrefaction was proposed as a mean to pretreat Leucaena leucocephala wood prior to fast pyrolysis process. Torrefaction was carried out in a continuous tubular flow reactor to produce torrefied biomass which was subsequently fast pyrolysed in a bubbling fluidised bed reactor to produce bio-oil, char and gas. Five different torrefaction temperatures (240, 260, 280, 300 and 320 C) were applied. The results showed that the torrefied biomass yields were 50-98% depending on the torrefaction severity. After fast pyrolysis process, the bio-oils were separated into two fractions (heavy and light fractions). The total bio-oil yields were reduced from 69% for non-torrefied biomass to 16% for biomass torrefied at 320 C and 64% for biomass torrefied at 240 C. Nevertheless, the heavy bio-oil yield appeared to increase from 30% for non-torrefied biomass to a maximum of 33% for biomass torrefied at 280 C. This corresponds to the increase of energy yield from 34 to 38%. Intriquingly, torrefaction of Leucaena leucocephala at 280 C was also proved to ameliorate the energy efficiency of fast pyrolysis process as up to 65% of energy in biomass could be recovered in the form of liquid and solid biofuels.